Posttraumatic stress and growth in adolescent childhood cancer survivors: Links to quality of life - Koutná, Veronika; Blatný, Marek; Jelínek, Martin (Frontiers in psychology, 2022)
Pediatric cancer can be considered an event potentially leading to posttraumatic stress symptoms (PTSS) as well as posttraumatic growth (PTG). While clinically significant levels of PTSS are rare in childhood cancer survivors, PTG is common in this population. However, the relationship of PTG to overall adaptation and quality of life (QOL) in pediatric cancer patients is not clear. Therefore, our study aims to analyse the relationships of PTSS and PTG with QOL in childhood cancer survivors. In this study, 172 childhood cancer survivors completed measures of quality of life (Minneapolis-Manchester Quality of Life Scale; child and adolescent version), posttraumatic stress (UCLA PTSD Reaction Index for DMS-IV) and posttraumatic growth (Benefit Finding Scale for Children). Correlation analyses were carried out separately for the child (up to 13 years, N = 47) and adolescent (more than 13 years, N = 125) groups and each QOL dimension. In the adolescent group, the relationship of PTSS and PTG with QOL was further verified by regression analyses while controlling for age, gender, and time off treatment. In children, negative relationships between PTSS and QOL were found, but the relationships between QOL and PTG were not significant. In adolescents, significant relationships were found for all dimensions of QOL and PTSS and also for several dimensions of QOL and PTG. The relationships between PTSS and QOL dimensions were negative in both groups, and the relationships between PTG and QOL in the adolescent group were weakly positive. In adolescents, regression analyses controlling for age, gender and time off treatment were performed and confirmed a negative relationship of PTSS with all QOL dimensions except for social functioning. For PTG, regression analyses revealed a significant positive relationship with QOL dimensions of social functioning, outlook on life and intimate relations. While the relationship between PTSS and QOL is negative for almost all QOL dimensions in children and adolescents, the nature of the relationship between PTG and QOL appears to be more complex and changing over time. PTG in children may reflect different processes with different outcomes than PTG in adolescents.